Blue light opens the ORAI1 LOC(K). (May 2021) - Srikanth, Sonal; Gwack, Yousang
Abstract: The current optogenetic tools to elevate cytoplasmic Ca 2+ concentrations either do not have high ion selectivity or activate undesirable signaling pathways. He et al. (2021) generated a light-operated Ca 2+ channel by integrating a photosensitive module directly into ORAI1 channels to selectively raise cytoplasmic Ca 2+ levels.